A comparative study of legislative and normative frameworks in Morocco, France and U.S.A towards progressive and evolutionary quality management in Moroccan laboratories - Kharrazi Anass; El Ftouh Sobha; El Feniche Mohammed; Bahji Mostafa; Bouaiti El Arbi (Romanian Journal of Laboratory Medicine)
Establishing and maintaining quality standards in medical laboratories is a significant challenge due to the rapid advancements in analysis techniques and technologies. In Morocco, the “Guide de Bonne Execution des Analyses’’ (GBEA) is the primary regulation framework overseeing quality assurance in laboratories. However, it does not adequately address potential gaps that could compromise patient safety.